Prevalence of Prothrombin G20210A, Factor V G1691A (Leiden), and Methylenetetrahydrofolate Reductase (MTHFR) C677T in Seven Different Populations Determined by Multiplex Allele-specific PCR - Hessner, Martin J.; Luhm, Robert A.; Pearson, Steven L.; Endean, Debra J.; Friedman, Kenneth D.; Montgomery, Robert R. (Thrombosis and Haemostasis, 1999)
Individuals belonging to six racial groups (African American, Asian Indian, Caucasian, Hispanic, Korean, Native American), and a seventh group comprised of referred patients with thrombosis were genotyped for the prothrombin G20210A mutation, the factor V G1691A (Leiden) mutation, and the methylenetetrahydrofolate reductase (MTHFR) C677T mutation by multiplexed allele-specific PCR. The prothrombin 20210A and factor V 1691A allele frequencies in the thrombosis patients, 3.2% and 9.5%, were significantly higher than those in the random Caucasians, 1.3% and 1.8%, (p = 0.043 and p <0.001, respectively). The relative risk of venous thrombosis was determined to be 2.4-fold for carriers of the prothrombin 20210A allele (odds ratio = 2.54; 95% confidence interval = 0.94, 6.82) and 4.5-fold for carriers of the factor V 1691A allele (odds ratio = 5.06; 95% confidence interval = 2.25, 11.36). Among the seven populations, significant differences were observed in the MTHFR 677T allele distribution, however this mutation was not determined to be a risk factor for venous thrombosis in the patient group studied, either alone or in combination with the pro-thrombin 20210A and/or the factor V 1691A allele(s).